2020
DOI: 10.3390/biom10030393
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Induces Inflammation in Retina and Brain

Abstract: Homocysteine (Hcy) is an amino acid that requires vitamins B12 and folic acid for its metabolism. Vitamins B12 and folic acid deficiencies lead to hyperhomocysteinemia (HHcy, elevated Hcy), which is linked to the development of diabetic retinopathy (DR), age-related macular degeneration (AMD), and Alzheimer’s disease (AD). The goal of the current study was to explore inflammation as an underlying mechanism of HHcy-induced pathology in age related diseases such as AMD, DR, and AD. Mice with HHcy due to a lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 68 publications
(48 reference statements)
5
81
0
3
Order By: Relevance
“…According to previous ndings, a high level of HCY did harm to systemic vascular endothelial cells [10,11]. Elsherbiny et al further demonstrated that HHCY can undermine inner and outer blood-retinal barriers [12]. We doubt that H-type hypertension may cause more serious retinal vessel lesions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to previous ndings, a high level of HCY did harm to systemic vascular endothelial cells [10,11]. Elsherbiny et al further demonstrated that HHCY can undermine inner and outer blood-retinal barriers [12]. We doubt that H-type hypertension may cause more serious retinal vessel lesions.…”
Section: Discussionmentioning
confidence: 95%
“…The patients in this study all suffered from hypertension, and the difference of retinal abnormalities were caused by HCY. However, whether HCY damages retinal vessels through the superposition effect of hypertension or directly damages retinal vessels remains controversial [4,12]. Serum HCY is a sulfur-containing amino acid, which is an important intermediate product produced during the metabolism of methionine and cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential biomarker related with DNA methylation in DR is homocysteine, of which high levels have been associated with increased risk of developing DR in diabetic patients, and with higher global DNA methylation probably linking it to altered metabolic memory phenomenon [248,249]. Interestingly, high homocysteine levels have been associated with increased inflammatory cytokines and activation of NF-kB [250].…”
Section: Dna Methylationmentioning
confidence: 99%
“…10 In addition, hyperhomocysteinemia was also reported to be associated with metabolic syndrome, obesity, insulin resistance, and inflammation. [11][12][13] Recent advances have demonstrated that there is a close link between hyperhomocysteinemia and several types of common cancers. [14][15][16][17] However, to our best knowledge, no report on the relationship between homocysteine and thyroid nodule prevalence has been published.…”
Section: Introductionmentioning
confidence: 99%